Single-atom silver induced amorphization of hollow tubular g-C3N4 for enhanced visible light-driven photocatalytic degradation of naproxen - Zhiwei Zhao; Wei Zhang; Liu, Wen; Yunyi Li; Jiangyu Ye; Jialiang Liang; Meiping Tong (Science of The Total Environment, 2020)
In this work, a novel strategy for building single-atom silver-induced amorphous graphitic carbon nitride (g-C3N4) with a hollow tubular morphology is developed. By forming a tubular supramolecular gel, silver is successfully isolated by the nitrogen atoms in both melamine and nitrate anions, impeding agglomeration in the subsequent thermal polymerization. The high density of single-atom-dispersed silver (atomic ratio up to 11.6%) selectively breaks the hydrogen bonds in layered g-C3N4, leading to a fully amorphous structure. Silver-induced full amorphization not only enhances the visible light absorption of g-C3N4 but also accelerates charge transfer, endowing the as-prepared photocatalyst having the optimal silver content with 52 times higher surface area specific naproxen (NPX) removal activity than pure g-C3N4. Both density functional theory (DFT) calculations and steric effects are applied to explain the degradation pathway of NPX. The toxicity of NPX is reduced by sufficient irradiation. This work provides useful insights into the design and morphology control of single metal ion-dispersed g-C3N4 for environmental applications.
Keywords: Amorphous carbon nitride; Detoxification; Hollow tubular morphology; Naproxen; Single-atom silver; Visible light-driven photocatalysis